Exploring the customer e-loyalty of millennials when purchasing footwear online in South Africa - Siphamandla Bingwa; Christine Frances De Meyer-Heydenrych; Mornay Roberts-Lombard (Cogent Business & Management, 2024)
Millennial purchases of footwear products online have grown in South Africa. Consequently, retailers in the country should develop increased knowledge of these consumers' online expectations to strengthen their satisfaction and future loyalty intentions. The study aimed to explore the factors influencing millennial consumers' e-satisfaction and e-loyalty when buying footwear online in South Africa. An enhanced understanding is required of the factors impacting millennial consumers' e-service experiences and e-trust behaviour, and their influence on e-satisfaction when purchasing footwear online. Data were collected from 248 respondents who bought footwear online over the past year. An online questionnaire and structural equation modelling were used to measure the hypotheses. In terms of the findings, website design secured the most significant impact on customer e-service experience, when buying footwear through an online platform. In addition, it was established that e-satisfaction significantly impacted millennial consumers' e-loyalty when buying footwear online. As such, it is imperative for online retailers targeting millennials to ensure a superior online shopping experience that will exceed their expectations. This will enhance the overall e-satisfaction experience of millennials and ultimately positively influence their attitudinal loyalty (AL) towards the retailer.Designer footwear has become the ultimate status symbol for millennials and this consumer cohort is spending more money on clothing and footwear than any other consumer cohort in South Africa (Morency, 2018). Footwear is starting to feature as a prominent segment in the online purchases of apparel among millennials (BMI, 2022, GlobalData, 2022; Statista, 2023).Millennials (born between 1985 and 2000) in South Africa are spending more money on clothing and footwear than any other consumer group (Biron, 2017; Shezi & Redda, 2022). This consumer cohort is fashion-conscious and has shown a strong preference for fashion brands (Eytan, 2019). According to Duggan (2021), millennials spend on average about one sixth of their monthly budget on clothing and footwear and are specifically purchasing online (Swiegers, 2018). To reach this target market, online retailers need to identify the online needs of this cohort through an understanding of e-service quality and e-trust to secure the e-satisfaction of the millennial market. Ting et al. (2016) concur stating that a positive e-service experience will increase customer satisfaction and result in repeat purchases. Superior e-service quality results in e-satisfaction, while e-trust enhances e-satisfaction (Purnamasari, 2018). As such when consumers (such as Millennials) are satisfied with an online retailer, this satisfaction creates the perception that the retailer is trustworthy (Chou et al., 2015; Krishnadas & Renganathan, 2022). Considering this, an understanding of the factors that influence millennials' e-service experience and e-trust behaviour and their impact on e-satisfaction is of importance to South African retailers. Specifically considering that it will enable online retailers to retain loyal customers and increase overall retailer profitability in the long term. The results of the statistical analysis revealed that e-service quality dimensions are an important element of online shopping that hs a significant positive influence on the e-service experience of millennial consumers online purchase of footwear. In addition, e-satisfaction was also found to be an important element of online shopping that has a significant positive influence on the attitudinal loyalty (AL) of millennial consumers purchasing footwear online. The main recommendations for online retailers is i) to invest in website personalisation functionalities that create a unique digital experience for an online visitor, ii) to incorporate price comparison features over promotional seasons to entice consumers to purchase from their online store over their competitors and iii) implement voice search functionalities to create real-time voice user interfaces and use live video chat services to update consumers on their purchase and the status of their orders.
Keywords: 650; E-service experience; E-security; E-privacy; E-trust; E-satisfaction; attitudinal loyalty; behavioural loyalty